The myth of green marketing : tending our goats at the edge of apocalypse - Smith, Toby Maureen, 1947- (University of Toronto Press, 1998)
"In this study, Toby Smith analyses the role that social myths such as green marketing play in public understanding of the environmental crisis." "This book introduces the concept of hegemony into environmental politics, using the concept to elucidate the political, economic, and social alliance that sustains our belief in industrial expansionism. The ecological crisis of the late twentieth century presents a challenge to the very foundations of this system. The hegemonic system reacts to a threat to its structure by producing social myths that provide a 'common sense' understanding of the threat. Smith examines one such social myth, the contemporary phenomenon known as green marketing, and how it came to reinforce, rather than challenge, the ethics of productivism. By analysing green marketing as it relates primarily to the early 1990s corporate campaigns of companies such as McDonald's, Shell, and Mobil, Smith demonstrates how these voices weave together an understanding of green consumerism using familiar language from economic and liberal democratic discourses."--Jacket.